Neurological Manifestations of Hospitalized Children with Influenza During the 2016–2017 Season. (4th October 2017) - Rao, Suchitra; Messacar, Kevin; Martin, Jan; Ahern, M Alex; Osborne, Christina; Torok, Michelle; Dempsey, Amanda; Schreiner, Teri; Dominguez, Samuel
Abstract: Background: Influenza A H1N1 and B are associated with neurological complications including seizures, encephalopathy and encephalitis. However, this season, when H3N2 was the predominant strain, many patients were admitted with neurological manifestations of influenza (NMI). The study objectives were to: 1) identify clinical characteristics of children with NMI and 2) compare demographics and clinical characteristics with influenza-positive controls. Methods: We conducted a retrospective cohort/case control study of children with NMI at Children's Hospital Colorado from Dec 2016-Apr 2017. We reviewed the medical records to identify children with NMI, and assessed clinical characteristics and outcomes. We conducted unadjusted conditional logistic regression using influenza-positive sex, race and time-matched controls to identify risk factors associated with NMI. Results: Of 126 inpatients with influenza, 20 (16%) had NMI; 11 (55%) had encephalopathy, meningitis or encephalitis, 13 (65%) had a seizure presentation, 4 children had both presentations (Table). Nineteen (95%) had infection with influenza H3N2. Of those with known vaccination status, 13/19 (68%) were unvaccinated against influenza. Compared with matched controls, children with NMI were more likely to have a neurological comorbidity, (40% vs 11%, OR 4.1, 95% CI 1.5–11.3) and a secondary bacterial infection (35% vs 13%, OR 4.2, 95% CI 1.2–15). Conclusion: NMI was associated with H3N2 strains, and most cases were brief, reversible, yet required intensive care. Our findings suggest consideration of influenza testing among febrile children with altered mental status/seizures, and the importance of influenza vaccination among children with underlying neurological disorders. Disclosures: S. Rao, GSK: Investigator, Research support; A. Dempsey, Merck, Pfizer, sanofi pasteur: Consultant, no research funding